Separate and Shared Neural Basis of Face Memory and Face Perception in Developmental Prosopagnosia - Liu, Xiqin; Li, Xueting; Song, Yiying; Liu, Jia (Frontiers in Behavioral Neuroscience, 2021)
Developmental prosopagnosia (DP), also known as face blindness, is a cognitive disorder with a severe deficit in recognizing faces. However, the heterogeneous nature of DP leads to a long-standing debate on which stages the deficit occurs, face perception (e.g., matching two consecutively-presented faces) or face memory (e.g., matching a face to memorized faces). Here, we used the individual difference approach with functional MRI to explore the neural substrates of DPs’ face perception and face memory that may illuminate DPs’ heterogeneity. Specifically, we measured the behavioral performance of face perception and face memory in a large sample of individuals suffering DP (N = 64), and then associated the behavioral performance with their face-selective neural responses in the core face network (CFN) and the extended face network (EFN), respectively. Behaviorally, we found that DP individuals were impaired in both face perception and face memory; however, there was only a weak correlation between the performance of two tasks. Consistent with this observation, the neural correlate of DPs’ face memory was localized in the bilateral fusiform face area, whereas DPs’ face perception was correlated with the face selectivity in the right posterior superior temporal sulcus, suggesting that the neural substrates in the CFN for face memory and face perception were separate in DP. In contrast, shared neural substrates of face perception and face memory were identified in the EFN, including the right precuneus and the right orbitofrontal cortex. In sum, our study provides one of the first empirical evidence that the separate and shared neural substrates were identified in the core and extended face networks respectively, which may help illuminating DP’s heterogeneous nature.